2022
DOI: 10.1055/s-0042-1745864
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Management of Pancreatitis Related Portal Hypertension

Abstract: Extrahepatic portal hypertension (EPH) is hypertension that occurs in the extrahepatic portal vasculature in the absence of liver cirrhosis. Portal hypertension (PHTN) is defined as a pressure gradient between the portal vein and hepatic vein/inferior vena cava (IVC) exceeding more than 5 mm Hg. PHTN is more commonly known as a manifestation of cirrhosis and the related elevation in hepatic to venous pressure gradient (HVPG); however, there are other extrahepatic etiologies to PHTN that are important for revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Therapeutic strategies for bleeding from LSPH include endoscopic interventions, partial splenic arterial embolization (PSAE), and splenectomy. 10 13 Endoscopic interventions are widely used for gastroesophageal varices in patients with liver cirrhosis but have a high failure rate in the management of GI bleeding caused by LSPH. 12 PSAE is a major therapeutic strategy for hypersplenism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therapeutic strategies for bleeding from LSPH include endoscopic interventions, partial splenic arterial embolization (PSAE), and splenectomy. 10 13 Endoscopic interventions are widely used for gastroesophageal varices in patients with liver cirrhosis but have a high failure rate in the management of GI bleeding caused by LSPH. 12 PSAE is a major therapeutic strategy for hypersplenism.…”
Section: Introductionmentioning
confidence: 99%
“… 10 13 Endoscopic interventions are widely used for gastroesophageal varices in patients with liver cirrhosis but have a high failure rate in the management of GI bleeding caused by LSPH. 12 PSAE is a major therapeutic strategy for hypersplenism. Some studies demonstrated that PSAE was an effective approach for GI bleeding caused by LSPH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation